Efektivitas Amelioran pada Tanah Pasiran untuk Meningkatkan Pertumbuhan dan Serapan NP Tanaman Jagung Manis - Astiko, W; Isnaini, M; Fauzi, M Taufik; Muthahanas, I (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Astiko W, Isnaini M, Fauzi, MT., & Muthahanas, I. (2023). Effectiveness of amelioran on sandy soil to increase growth and uptake of NP by sweet corn. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 78-87). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Sandy soil, which is porous and has a very low water holding capacity, is the main obstacle to increasing soil fertility and the growth of sweet corn plants. This study aimed to determine the effectiveness of several types of ameliorants in increasing the growth and uptake of NP nutrients by sweet corn plants in sandy soil. The research was conducted in Moncok Karya, Pejeruk Karya Village, Ampenan District, and Mataram City from May to July 2023. The experiment was arranged using a randomized block design consisting of five ameliorant treatments, namely PO: Control (without ameliorant), PA: rice husk charcoal, PK: compost, PS: cow manure, and PC: a mixture of rice husk charcoal, compost, and cow manure (1:1:1) with a dose of 20 tons/ha. The results showed that the mixture of ameliorant rice husk charcoal, compost, and cow manure had an effect on the height and number of leaves of sweet corn plants at 2, 4, and 6 WAP, stover weight per plant, nutrient uptake, and mycorrhizal development. Application of 20 tons per ha of mixed ameliorant increased plant height, number of leaves, the concentration of available P, and total N in the soil, N and P uptake by plants, the number of spores and root colonization, and the weight of wet and dry stover plants in sandy soil. Amelioran formulation of a mixture of 25% cow manure + 25% compost + 25% rice husk charcoal provides the highest concentration of soil nutrients, plant nutrient uptake, and growth of sweet corn.